2024
DOI: 10.3390/medicina60010123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Remimazolam on Pain Perception and Opioid-Induced Hyperalgesia in Patients Undergoing Laparoscopic Urologic Surgery—A Prospective, Randomized, Controlled Study

Cheol Lee,
Junsung Lim,
Hansol Hong
et al.

Abstract: Background and Objectives: The effects of midazolam, a benzodiazepine, on pain perception are complex on both spinal and supraspinal levels. It is not yet known whether remimazolam clinically attenuates or worsens pain. The present study investigated the effect of intraoperative remimazolam on opioid-induced hyperalgesia (OIH) in patients undergoing general anesthesia. Materials and Methods: The patients were randomized into three groups: group RHR (6 mg/kg/h initial dose followed by 1 mg/kg/h remimazolam and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Remifentanil consumption during surgery was notably higher in group R compared to group P. Despite concerns about opioid-induced hyperalgesia (OIH), our study showed that group R experienced less pain intensity compared with group P while resting in the PACU. This discrepancy is likely attributed to the effects of remimazolam on GABA receptors, potentially affecting pain perception [36]. While one might anticipate delayed recovery time, increased pain intensity due to OIH, and frequent use of rescue analgesics in group R, which received higher doses of remifentanil, the remimazolam group remarkably exhibited more favorable outcomes in these aspects in this study.…”
Section: Discussionmentioning
confidence: 71%
“…Remifentanil consumption during surgery was notably higher in group R compared to group P. Despite concerns about opioid-induced hyperalgesia (OIH), our study showed that group R experienced less pain intensity compared with group P while resting in the PACU. This discrepancy is likely attributed to the effects of remimazolam on GABA receptors, potentially affecting pain perception [36]. While one might anticipate delayed recovery time, increased pain intensity due to OIH, and frequent use of rescue analgesics in group R, which received higher doses of remifentanil, the remimazolam group remarkably exhibited more favorable outcomes in these aspects in this study.…”
Section: Discussionmentioning
confidence: 71%